1981
DOI: 10.1017/s0021859600066181
|View full text |Cite
|
Sign up to set email alerts
|

The effects of seed size, autumn nitrogen and plant population density on the response to delayed sowing in winter oil-seed rape (Brassica napus)

Abstract: The aim of the experiments reported here was to investigate the possibility of minimizing yield losses due to late sowing by increasing leaf area and radiation interception during the pre-flowering period. The use of large seed did increase leaf area, radiation interception and crop weight at flowering. Normally this would be expected to lead to increased yield of late sowings, but hot, dry conditions severely affected all crops during seed growth. Applying fertilizer nitrogen in the seed bed boosted pre-flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
1
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 5 publications
8
41
1
1
Order By: Relevance
“…In cultivars of B. rapa (Ahmed and Zuberi 1973;Elliott et al 2007) and B. oleracea (Heather and Sieczka 1991), plants grown from large seeds yielded more than plants grown from small seeds. In contrast, the size of planted seed had no effect on yield of spring and winter types of B. napus (Major 1977;Mendham et al 1981). In our study, seed size had a significant effect on yield of B. napus cultivars grown without insecticides.…”
Section: Elliott Et Al * Seed-size Evaluations In Argentine Canola 215contrasting
confidence: 82%
See 2 more Smart Citations
“…In cultivars of B. rapa (Ahmed and Zuberi 1973;Elliott et al 2007) and B. oleracea (Heather and Sieczka 1991), plants grown from large seeds yielded more than plants grown from small seeds. In contrast, the size of planted seed had no effect on yield of spring and winter types of B. napus (Major 1977;Mendham et al 1981). In our study, seed size had a significant effect on yield of B. napus cultivars grown without insecticides.…”
Section: Elliott Et Al * Seed-size Evaluations In Argentine Canola 215contrasting
confidence: 82%
“…Under dry conditions and high flea beetle damage, establishment of summer turnip rape, B. rapa, was 5Á6% higher with large seeds than with small seeds (Elliott et al 2007). Previous investigations have shown that seed size has a significant effect on seedling vigour in wild radish, Raphanus raphanistrum L. (Choe et al 1988), wintertype B. napus (Mendham et al 1981), spring-type B. napus (Major 1977;Bodnaryk and Lamb 1991) and B. rapa (Elliott et al 2007). Seedlings from large seeds had larger cotyledons, larger true leaves and greater weight than seedlings of small seeds.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rapeseed typically gives similar yields over a wide range of sowing rate (Mendham et al 1981b, Nuttall et al 1992). However, plants at higher density are thinner and carry fewer branches, crops growth rates and net assimilation rates are smaller.…”
Section: Stand Population Densitymentioning
confidence: 99%
“…However, plants at higher density are thinner and carry fewer branches, crops growth rates and net assimilation rates are smaller. The individual leaf area per plant in the high density is 3-4 times smaller than in the low densities (Mendham et al 1981b, Morrison et al 1990. Therefore could be possible that stand population density can influence nitrogen concentration in plants and their yield.…”
Section: Stand Population Densitymentioning
confidence: 99%